Protocol for live imaging of axonal transport in iPSC-derived iNeurons - Dan Dou; Erika L.F. Holzbaur; C. Alexander Boecker (STAR Protocols)
Summary: Studies of human induced pluripotent stem cell (iPSC)-derived neurons promise important insights into neurodegenerative diseases. Here, we present a protocol for live imaging of axonal transport in glutamatergic iPSC-derived neurons (iNeurons). We describe steps for the differentiation of iPSCs into iNeurons via PiggyBac-mediated neurogenin 2 (NGN2) delivery, iNeuron culture and transfection, and the acquisition and analysis of time-lapse images. Our protocol is optimized for the widely available catalog of KOLF2.1J iPSCs with mutations relevant to neurodegenerative diseases but is also applicable to other iPSC lines.For complete details on the use and execution of this protocol, please refer to Dou et al.1,2 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.